2019
DOI: 10.3389/fpsyg.2019.01728
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Counterintuitiveness in Supernatural Agent Dream Imagery

Abstract: The present article tests counterintuitiveness theory and methodology in relation to religious dream imagery using data on religious dream content. The endeavor adopts a “fractionated” or “piecemeal” approach where supernatural agent (SA) cognition is held to be a pivotal building block of purportedly religious dreaming. Such supernaturalistic conceptualizations manifest in a cognitive environment of dream simulation processes, threat detection, and violation of basic conceptual categorization characterized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 104 publications
(151 reference statements)
1
10
0
Order By: Relevance
“…Dream representation is partly inspired by, framed by and bears a strong resemblance with the supernatural representations that prevail in the dreamer's cultural and religious environment (during the waking state). As the data from the present research indicates (below) and (Nordin & Bjälkebring, 2019), this strongly suggests that such input from the waking state and the religious allusions from dreamers' cultural environment is considerable.…”
Section: Sa/ci Dreams Selection Into Waking Cultural Transmission and Dpsr Theorysupporting
confidence: 69%
See 2 more Smart Citations
“…Dream representation is partly inspired by, framed by and bears a strong resemblance with the supernatural representations that prevail in the dreamer's cultural and religious environment (during the waking state). As the data from the present research indicates (below) and (Nordin & Bjälkebring, 2019), this strongly suggests that such input from the waking state and the religious allusions from dreamers' cultural environment is considerable.…”
Section: Sa/ci Dreams Selection Into Waking Cultural Transmission and Dpsr Theorysupporting
confidence: 69%
“…Dreams may accordingly be effective means for the cultural transmission and spreading of religious ideas (Knafo & Glick, 2000). Research on religion, dreaming and allegedly "mystical experiences" demonstrates that REM (NREM) sleep generates religious beliefs such as the existence of supernatural agents or "SA cognitions" (McNamara et al, 2018;McNamara, 2016), and that SA cognition in religious dreaming manifests (minimally) counterintuitive imagery (MCI) (Nordin, 2020;Nordin & Bjälkebring, 2019). The present article adopts contemporary models in cognitive and evolutionary anthropology and the study of religion to recast some of the notions of DPSR theory by exploring SA cognition, MCI phenomena and theory in relation to "religious dreaming".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…comment partly addresses the main purpose of our article (Nordin and Bjälkebring, 2019) about counterintuitiveness in dreaming. While we recognize that his remarks include some constructive points about the presented research results and highlight some possible limitations in the theoretical summary and modeling of supernatural agent (SA) cognition in dreaming, we take issue with other points and with the way our arguments are framed.…”
mentioning
confidence: 95%
“…Investigating further the frequency and characteristics of LD in religious and non-religious communities could make a good sense in evaluating changes in locus of control (LOC), the degree to which people believe that they, as opposed to external forces, have control over the outcome of events in their lives (Rotter, 1966 ) in association with dreaming and with LD, in particular (Blagrove and Hartnell, 2000 ). A recent study demonstrated high prevalence of supernatural agent in dream imagery among Hindu Nepalese informants (Nordin and Bjälkebring, 2019 ).…”
mentioning
confidence: 99%